The Immunology of Macrophage Activation Syndrome - Crayne, Courtney B.; Albeituni, Sabrin; Nichols, Kim E.; Cron, Randy Q. (Frontiers in Immunology, 2019)
Synonymous with secondary hemophagocytic lymphohistiocytosis, macrophage activation syndrome (MAS) is a term used by rheumatologists to describe a potentially life-threatening complication of systemic inflammatory disorders, most commonly systemic juvenile idiopathic arthritis (sJIA) and systemic lupus erythematosus (SLE). Clinical and laboratory features of MAS include sustained fever, hyperferritinemia, pancytopenia,fibrinolytic coagulopathy, and liver dysfunction. Soluble interleukin-2 receptor alpha chain (sCD25) and sCD163 may be elevated, and histopathology often reveals characteristic increased hemophagocytic activity in the bone marrow (and other tissues), with positive CD163 (histiocyte) staining. A common hypothesis as to the pathophysiology of many cases of MAS proposes a defect in lymphocyte cytolytic activity. Specific heterozygous gene mutations in familial HLH-associated cytolytic pathway genes (e.g., PRF1, UNC13D) have been linked to a substantial subset of MAS patients. In addition, the pro-inflammatory cytokine environment, particularly IL-6, has been shown to decrease NK cell cytolytic function. The inability of NK cells and cytolytic CD8 T cells to lyse infected and otherwise activated antigen presenting cells results in prolonged cell-to-cell (innate and adaptive immune cells) interactions and amplification of a pro-inflammatory cytokine cascade. The cytokine storm results in activation of macrophages, causing hemophagocytosis, as well as contributing to multi-organ dysfunction. In addition to macrophages, dendritic cells likely play a critical role in antigen presentation to cytolytic lymphocytes, as well as contributing to cytokine expression. Several cytokines, including tumor necrosis factor, interferon-gamma, and numerous interleukins (i.e., IL-1, IL-6, IL-18, IL-33), have been implicated in the cytokine cascade. In addition to broadly immunosuppressive therapies, novel cytokine targeted treatments are being explored to dampen the overly active immune response that is responsible for much of the pathology seen in MAS.